(untitled) (International Journal of Nursing Education, 2020)
Background: Homelessness is a public health issue across nations. The 2011 Indian national census estimated 1.77 million men, women and children living without shelter. The US Department of Housing and Urban Development found 567,715 homeless people representing a cross-section of America. Purpose: The purpose of this qualitative descriptive study was to examine the structures, processes and critical success factors (CSF) of free and volunteer clinics in Kansas City. Methodology: A qualitative research design using a holistic multiple case study method was used to examine a purposive sample of five safety net clinics in an urban Midwestern state. Data were collected through participant observation and semi-structured interviews. The data were analyzed for common themes that describe the clinics’ structures, processes and critical success factors. Results: The clinics’ missions, structures, processes and outcomes varied. Mission focus with dignity and respect and staffing with proper resources and stewardship were the dominant themes. Five subthemes arrived from the narratives: Mission is critical to the viability of the clinic, preserving human dignity, volunteers are treasured,adapting to meet evolving needs, and money matters. Conclusion: The results suggest that a mission fostering person-centered care, dignity and respect for humanity impact the success of safety-net clinics, especially for the homeless population. The results will lead in creating a model safety net clinic in Vellore district.